The Effectiveness of Digitizing Land Services to Prevent Land Mafia in Vietnam - Thá, Nguyán Háu; bin Idrus, Datuk Mazlee Malik (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
This research aims to analyze: 1) Implementation of digitization of land services. 2) Effectiveness of digitizing land services to prevent land mafia. The approach method used in this research is a sociological juridical approach. The research specifications used are analytical descriptive research. This type of data uses primary data and secondary data obtained through interviews and literature study. The data analysis method used in this research is descriptive analysis. The research results were concluded: 1). The implementation of digitization of land services is carried out through a special agrarian internet site. Currently, the Ministry of Agrarian Affairs has implemented four digital land services, including Electronic Mortgage Rights, checking certificates, Land Registration Certificates, and Land Value Zone information. There are two electronic services that will be added by the AGRARIAN Ministry, namely land sale and purchase deeds and transfer of rights. The implementation of digitalization of land services at AGRARIAN AGENCY Vietnam, apart from using a special agrarian internet site, is also carried out through the Touch application. Touch My Land is an application created to answer various community land problems. 2) The effectiveness of digitizing land services to prevent land mafia can effectively prevent land mafia practices and achieve the strategic goals of the Ministry of Agrarian Affairs.